Nanotechnology And Cancer : An Overview - SUBBIAH BALAJI; B PARIMALA DEVI (International Journal of Pharma and Bio Sciences, 2010)
Nanotechnology is a new direction in science and technology, which is intensively developed during the last decade and represents one of the most important directions in the technological developments of the leading countries in 21st century. Nanotechnologies significantly influence all aspects of our life. Their commercial use involves all branches of industry, medicine and agriculture. The use of nanoparticulate pharmaceutical carriers to enhance the in vivo efficiency of many drugs well established itself over the past decade both in pharmaceutical research and clinical setting.This review focuses nanotechnology in Nanocryosurgery , Photodynamic Therapy, DNA-binding by functionalized Gold nanoparticle, Quantum Dots,Polymers as Nanovectors , Polymeric Micelles , Liposomes and Dendrimers.